PENDIDIKAN POLITIK BAGI PEMUDA SEBAGAI HAK PEMENUHAN DEMOKRASI KECAMATAN ALALAK, BARITO KUALA - Muhammad Abdurrohim; Radita Gora Tayibnapis; Jerry Indrawan; Putrawan Yuliandri; Ermita Ekalia; Andina Mustika Ayu (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities with the theme of political education targeting youth in Handil Bakti Urban Village as target groups in the form of socialization. This service activity is included in the direct political socialization theme like the development of Indonesia politics, media and politics and political communication because the evolution of Indonesian political campaign nowadays. Survey and socialising are the two steps of this service's implementation. The survey was conducted to learn more about the target group's perceptions of political engagement, and the socialisation process sought to improve political literacy and raise awareness of young people's responsibilities as citizens. Because political engagement is one of the key indicators of democracy and is crucial to renewing a nation's democratic spirit, the goal of this political education is to increase both the quantity and quality of involvement in the election cycle.